The Influence of Attitude, Subjective Norms, and Behavioral Control on the Intention to Choose Islamic Banks with Islamic Religiosity as a Moderating Variable (Case Study on BRI Syariah Customers in Purwokerto) - Najakh, Akhmad Khoyrun; Astogini, Dwiwiyati; Martini, Sri (Journal of Economicate Studies, 2018)
This study aims to analyze the influence of attitudes on the intention to choose Islamic banks, the effect of subjective norms on the intention to choose Islamic banks, the effect of behavioral control on the intention to choose Islamic banks, and the moderating role of religiosity in the relationship between attitudes, subjective norms, behavioral control, and the intention to choose Islamic banks. The method used was a survey with purposive sampling of 100 respondents. The data analysis tool used was multiple regression analysis with SPSS 16.0 software. The results of this study conclude that attitudes do not influence the intention to choose Bank BRISyariah. Subjective norms have a positive effect on the intention to choose Bank BRISyariah. Behavioral control does not influence the intention to choose Bank BRISyariah. The relationship between attitudes, subjective norms, and behavioral control with the intention to choose Bank BRISyariah is not moderated by religiosity. Based on these conclusions, Bank BRISyariah is advised to improve understanding related to subjective norms to increase the number of customers using Islamic banking services. Further research is recommended to develop this study by exploring both independent and dependent variables before and after behavioral intention or specific action intentions.